Effects of Catastrophic Insect Outbreaks on the Harvesting Solutions of Dahurian Larch Plantations - Qi Jin; Lauri Valsta; Kari Heliövaara; Jing Li; Youqing Luo; Juan Shi (International Journal of Forestry Research)
Optimal harvesting under pest outbreak risk was studied on a set of even-aged Dahurian larch (Larix gmelinii) stands in northeastern Inner Mongolia, China. The effects of catastrophic pest outbreaks caused by the Siberian moth (Dendrolimus sibiricus) on the economic harvesting plan are compared through both deterministic and stochastic cases. Stand simulation is based on an individual-tree growth system. A scenario approach is applied when simulating the effects of catastrophic pest outbreaks. Insect damage is assumed to be a Poisson process with an average rate of 0.1 per year. One hundred scenarios of insect damage are created using the Poisson process to simulate the distribution of bare land value of each of the optimal regimes. Numerical results show that the optimal rotation is shortened with an increasing probability of a catastrophe. The average bare land values in the stochastic case are approximately 14.8% to 22.9% lower. Numbers of thinnings are decreased for most plots when seeking a highest bare land value, compared to the deterministic optima. If given a constant thinning rate, increasing risk-taking shortens the optimum rotation, as the model set used.